Brexodus and the Commercial Real Estate Markets of London and Paris - Susan Ball (Revue Française de Civilisation Britannique)
This paper draws on recent conceptual work in the field of border studies in order to analyse the island economy - of which London and Paris are a part - as a dynamic functional process of bordering. The particular focus is on the commercial real estate markets of the two cities, and the discourse of firms of international property consultants. It is shown that these non-state actors play a key role in standardising information so that investors perceive the office markets of global cities as transparent. A brief account is given of the evolution of these cross-border consultancy relations since Big Bang in 1986 and in the context of the financialisation of real estate. The paper then goes on to examine research reports and commentaries published since the 2016 United Kingdom European Union membership referendum by the three leading firms of property consultants covering the London and Paris office markets. This was a period marked by much speculation about the transfer of jobs (Brexodus) in financial services from London to Paris. For international investors in real estate, Brexit added a new variable to their calculations of risk, and one that seemingly muddied the waters of the relatively transparent property markets of London and Paris. The analysis of market commentaries concludes that the international network of glocal property consultants plays a role in the on-going process of bordering and filtering flows of finance that reflect the normative power of international real estate investors.